Global virtual reality safety test acceptance in gastronomy tourism economy sustainability - Saad, Mazni; James Pratt, Thomas; Jeinie, Mohammad Halim; Mohamad Najib, Muhammad Danial Haiqal (IMBR, 2025)
The burgeoning gastronomy tourism sector has witnessed an uptick in workplace accidents, exacerbating concerns about the safety of workers, especially those new to the commercial kitchen environ ment. T heir la ck of experi ence often transl ates into diffi cu lty in ident ifying and addre ssing potential hazards. Responding to this urgent problem, an acceptance test was carried out. The purpose of this assessment was to evaluate, in culinary environments, the efficiency of a simple but immersive simulation c alled Culinary Safety Virtual Tour Hazard Identification Training Tools (VT-HiTT) in reducing and analyzing hazards. Underlining the transforming power of Virtual Reality (VR) technology in strengthening safety procedures across the hotel industry, the validation process run by commercial kitchen professionals, focused on quant itative evalu ations , gave impo rtant new perspe ctiv es o n the g eneral ad opt ion of v irtual reality among professionals and acknowledged the natural limits of simply qualitative methods. The largely favorable comments highlight VR's exciting path in raising workplace safety standards. These positive results significa ntly ins pire legisla tors to inc lud e VR smo othly into s afety training progr ams desig ned espec ially for indu strial kitc hens. Such proac tive initi atives will s urely help to signific antly r educe haz ards and pro mote a strong safety culture all around the gastronomy industry.